Toxicological impact of strobilurin fungicides on human and environmental health: a literature review - Leite, Fernanda Gomes; Sampaio, Carolina Ferreira; Cardoso Pires, Janaína Aparecida; de Oliveira, Danielle Palma [UNESP]; Dorta, Daniel Junqueira [UNESP] (Taylor & Francis, 2024)
Fungicides are specifically used for controlling fungal infections. Strobilurins, a class of fungicides originating from the mushroom Strobilurus tenacellus, act on the fungal mitochondrial respiratory chain, interrupting the ATP cycle and causing oxidative stress. Although strobilurins are little soluble in water, they have been detected in water samples (such as rainwater and drinking water), indoor dust, and sediments, and they can bioaccumulate in aquatic organisms. Strobilurins are usually absorbed orally and are mainly eliminated via the bile/fecal route and urine, but information about their metabolites is lacking. Strobilurins have low mammalian toxicity; however, they exert severe toxic effects on aquatic organisms. Mitochondrial dysfunction and oxidative stress are the main mechanisms related to the genotoxic damage elicited by toxic compounds, such as strobilurins. These mechanisms alter genes and cause other dysfunctions, including hormonal, cardiac, neurological, and immunological impairment. Despite limitations, we have been able to compile literature information about strobilurins. Many studies have dealt with their toxic effects, but further investigations are needed to clarify their cellular and underlying mechanisms, which will help to find ways to minimize the harmful effects of these compounds.
Keywords: environmental; non-target toxicity; oxidative stress; Strobilurins